On Anthimus and his work - Kokoszko, Maciej (Vox Patrum, 2022)
In the Church Fathers’ teachings there are numerous references to medical knowledge, including those concerning dietetics. They were, however, not meant to be used to heal the faithful but they were a resource of morally elevating metaphors appropriate in preaching Christian ethics. The first fully extant work on dietetics penned by a Christian author is entitled De observatione ciborum. It is a Latin collection of dietetic advice addressed to Teuderich, ruler of the Franks (6th c. AD). Its author, Anthimus, was a Greek physician exiled from Constantinople, first seeking refuge among the Arrian Goths, and later sent to the Catholic Franks on diplomatic missions. The present article provides a fuller picture of Anthimus’ medical competence and shows arguments to pinpoint the date of compiling the treatise. The analysis is based on three entries of the treatise, namely Chapters 25, 26 and 33. The method adopted in the research is a heuristic analysis of Anthimus’ work, and select, mainly medical, literature. The author of the present study argues that the work was composed in the Constantinopolitan milieu after 508, possibly circa 511. Its author was a competent physician, able to creatively apply theories he learned.